Medical management of the surgical patient a textbook of perioperative medicine - Lubin, Michael F. 1947-; Smith, Robert B. 1933- (Cambridge University Press, 2006)
This comprehensive textbook, now fully revised, rewritten and updated in its fourth edition, provides an authoritative account of all aspects of perioperative care for surgical patients. All areas of medical disease are discussed with clear recommendations for work up and management in the perioperative period. Basic discussions of surgical procedures are included to help non-surgeons understand the procedures and their implications for patient care. This definitive account includes numerous contributions from leading experts at national centers of medical excellence. It will serve as a significant work of reference for internists, anesthesiologists and surgeons